Technical Design Report for a Carbon-11 Treatment Facility - Penescu, Liviu; Stora, Thierry; Stegemann, Simon; Pitters, Johanna; Fiorina, Elisa; Augusto, Ricardo Dos Santos; Schmitzer, Claus; Wenander, Fredrik; Parodi, Katia; Ferrari, Alfredo; Cocolios, Thomas E. (Frontiers in Medicine, 2022)
Particle therapy relies on the advantageous dose deposition which permits to highly conform the dose to the target and better spare the surrounding healthy tissues and organs at risk with respect to conventional radiotherapy. In the case of treatments with heavier ions (like carbon ions already clinically used), another advantage is the enhanced radiobiological effectiveness due to high linear energy transfer radiation. These particle therapy advantages are unfortunately not thoroughly exploited due to particle range uncertainties. The possibility to monitor the compliance between the ongoing and prescribed dose distribution is a crucial step towards new optimizations in treatment planning and adaptive therapy. The Positron Emission Tomography (PET) is an established quantitative 3D imaging technique for particle treatment verification and, among the isotopes used for PET imaging, the 11C has gained more attention from the scientific and clinical communities for its application as new radioactive projectile for particle therapy. This is an interesting option clinically because of an enhanced imaging potential, without dosimetry drawbacks; technically, because the stable isotope 12C is successfully already in use in clinics. The Medicis-Promed network led an initiative to study the possible technical solutions for the implementation of 11C radioisotopes in an accelerator-based particle therapy center. We present here the result of this study, consisting in a Technical Design Report for a 11C Treatment Facility. The clinical usefulness is reviewed based on existing experimental data, complemented by Monte Carlo simulations using the FLUKA code. The technical analysis starts from reviewing the layout and results of the facilities which produced 11C beams in the past, for testing purposes. It then focuses on the elaboration of the feasible upgrades of an existing 12C particle therapy center, to accommodate the production of 11C beams for therapy. The analysis covers the options to produce the 11C atoms in sufficient amounts (as required for therapy), to ionize them as required by the existing accelerator layouts, to accelerate and transport them to the irradiation rooms. The results of the analysis and the identified challenges define the possible implementation scenario and timeline.